Рейтинг закладів вищої освіти як важлива складова їхнього іміджу - Остапйовський, Ігор; Остапйовська, Тетяна (My University, 2018)
У статті розкрито важливість іміджу закладів вищої освіти в умовах конкурентного середовища. На основі порівняльного аналізу дано визначення іміджу закладу вищої освіти. Встановлено, що важливою складовою іміджу є рейтинг закладу освіти. Проаналізувавши міжнародні та вітчизняні підходи, обґрунтовано авторське бачення методології та методики проведення рейтингових досліджень на макро та мезо рівнях. The urgency of the research problem was substantiated in the article. Meanings of concepts of image and image of the institution of higher education were defined. The image was viewed as an image of a certain object that has been purposefully formed in the mass consciousness. Components of the image of institutions of higher education were determined. They are factors of external and internal impact. Factors of external impact are: appearance, infrastructure and attributes of the establishment; status and form of ownership; financial opportunities; employment of graduates; reputation of the leader; the popularity of the institution among the public and in professional circles; presence of famous and welknown students and graduates; mention in the media and the Internet; reviews of alumni, their relatives and friends; the rating of the educational institution in the region and the in state. Internal factors are: the presence of a mission, strategy, and a clear concept of development; quality of educational process; dynamics and level of professional skill of teachers; moral and psychological climate in the team; the nature of the relationship in the team: administration – teachers, administration – students, administration – the public, teachers – students, teachers – the public; introduction of innovations; traditions; level of leisure and educational work; integration into the European and world educational space. It was established that the rating of the institution is an important factor in the formation of the image. According to the results of scientific search, the author's vision of criteria and indicators of rating determination was disclosed.
Keywords: заклад вищої освіти; імідж закладів вищої освіти; рейтинг закладів вищої освіти; establishment of higher education; image of establishments of higher education; rating of establishments of higher education